O brincar das crianças da Região Metropolitana do Recife (RMR) durante a pandemia da Covid-19 - Oliveira, Hacsa Priscila Soares de (2022)
This research aimed to understand how the experiences of children in the Metropolitan Region of Recife (RMR) play, before and during the Covid-19 pandemic, based on the dispositional and contextual sociology of Bernard Lahire (2004). With the specific objectives of mapping how children's play experiences occur, understanding the impact of the pandemic on children's play and reporting children's perception of the coronavirus quarantine. Assuming that children are social actors (SIROTA, 2001), this research aimed to hear what children had to say about the construction of their playful dispositions. In this sense, the analysis of the playful dispositions allowed us to understand the sociability dynamics of these subjects, as well as the impact of the Covid-19 pandemic on these dynamics. Methodologically, the research was carried out through interviews through video calls on WhatsApp and Google Meet platforms. That said, the data collected were analyzed in the Atlas.ti program, based on the coding of the categories raised in the research based on Friese (2012) and Saldaña (2013).